Studies on the effect of agitation and aeration for the improved protease production by bacillus licheniformis NCIM-2042. (2016) - Dey, Apurba; Bhunia, Biswanath; Dutta, Subhasish
Abstract: The present research work deals with the effect of agitation and aeration for protease production using Bacillus licheniformis NCIM-2042 . The experiments were carried out in a lab scale 2.2 l bioreactor with 2 l working volume at 37 °C for 84 hour. Determination of kL a was estimated by dynamic gassing out method. The value of kL a was found to be 41, 54 and 56 1/h at 1, 2 and 3 vvm of airflow rate respectively. The maximum protease production was found to be 382.46 U at optimum flow rate of 2 vvm and agitation speed of 180 rpm.